SME Loan Pricing and Lending Relationships in Germany: A New Look - Erik Lehmann; Doris Neuberger (Universität Rostock, Institut für Volkswirtschaftslehre, 1998)
Strong lending relationships between banks and small and medium-sized enterprises (SMEs) play a key role in the bank-based financial system of Germany. So far, they have been mainly described by the notion of an housebank and transactional features of long-term bank-customer relationships. The present paper takes a new look by considering also interactional variables which try to measure social relations between loan officer and firm manager. We find that these variables do affect loan pricing, but that their influence varies according to firm age and housebank status.
Keywords: G2; L2; 330; Banking; Relationship Lending; Small Business Finance; Kredit; KMU; Bank; Lieferanten-Kunden-Beziehung; Betriebliche Preispolitik; Theorie; Deutschland